Digging up the past - Woolley, Leonard, Sir, 1880-1960. (Harmondsworth, UK : Penguin Books Limited, 1937)
" An introduction to archaeology showing how excavation has grown from a treasure hunt to a science". - cover.
"First published 1930".
Author's note : "This little book is based on a series of six talks broadcast by the B.B.C., to whom I am indebted for permission to re-publish the substance in permanent form."
Includes index.
Keywords: Excavations (Archaeology)